The Actualization of Legal Connectivity at Sea Between Indonesia and the Philippines: A Comparative Study - Jannah, Miftahul; Amri, Ulil; Rahman, Mujibur; Irwan, Irwan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research is motivated by the issue of fragmentation of authority and jurisdictional uncertainty in Indonesian maritime law enforcement, particularly when maritime crimes involve both civilian and military elements simultaneously (connectivity cases). The research method uses a normative juridical approach and comparative law (comparative law approach), by analyzing legislation, legal doctrine, and institutional policies of maritime law enforcement in Indonesia and the Philippines. The analysis shows that the Indonesian system remains pluralistic and overlapping, while the Philippines has successfully established a centralized maritime law enforcement system through the Philippine Coast Guard (PCG) as a single civilian institution that prioritizes the principle of primacy of civil jurisdiction. The research findings emphasize the need for structural, normative, and value reforms to strengthen the supremacy of civil law in Indonesian waters, including strengthening the role of the Prosecutor's Office as dominus litis, revising the provisions of the Criminal Procedure Code and the Military Court Law and consolidating maritime law enforcement functions under the Maritime Security Agency. Thus, this research contributes to the development of an institutional and procedural model for handling connectivity cases at sea that is more effective, fair and in line with the principles of the rule of law at sea